IMPLEMENTASI STRATEGI MARKETING MIX DALAM MEMPERTAHANKAN USAHA (STUDI KASUS PADA ES KELAPA MUDA PAK AMBON DR. CIPTO SEMARANG) - Wijayanti, Ratna; Ariyanti, Septiarini (Fakultas Ekonomi, Universitas Semarang, 2022)
This study was conducted in Warung Es Kelapa Muda Pak Ambon Semarang. The purpose of this study was to determine out how marketing mix strategies were used in Warung Es Kelapa Muda Pak Ambon, and what factors helped and hindered it.The study used qualitative method of case study. With data collection using in-depth interview techniques, direct observation and documentation. To test the credibility of data, it used triangulation of data sources and triangulation of data collection techniques. The source of research data in in-depth interview was participant who have a position or authority on the object of the study, namely as many as 5 (Five) participants based on the principles of appropriateness and adequacy.From the results of this study, it shows that the implementation of marketing mix strategy has been done quite well and can increase sales of the products being sold. It is concluded that product quality, pricing, selection of promotional media, and sales locations play an important role in determining marketing strategy. The most powerful supporting factors are the characteristic taste of the product and location. Meanwhile, the most important inhibiting factors are promotion and weather changes.